Calculer la sémantique avec le langage IEML - Pierre Lévy (Humanités Numériques)
This paper presents IEML (Information Economy MetaLanguage), a uniform representation of human meaning and knowledge that can be read and processed automatically by machines. Distinguished from pragmatic and referential semantics, linguistic semantics is today incompletely formalised. Only its syntagmatic dimension has been mathematised in the form of regular languages. Its paradigmatic dimension remained to be formalised. To solve the problem of the complete mathematising of language, including its paradigmatic dimension, I propose to code the linguistic meaning in IEML. IEML has the same expressive capacity as a natural language and has an algebraic structure allowing the calculation of its semantics. The article explains its dictionary, its formal grammar, and its integrated tools for building semantic graphs. As far as its applications are concerned, IEML could be the vector of a fluid calculation and communication of meaning – semantic interoperability – capable of decompartmentalising the digital memory and feeding the progress of collective intelligence, artificial intelligence, and digital humanities. I conclude by indicating some research directions. This paper presents a synthesis of several decades of research.